Keefektifan Kepemimpinan Perempuan sebagai Kepala Sekolah - Mien Ratoe Oedjoe (Universitas Negeri Malang, 2016)
This study focused on describing the leadership effectiveness of female headmasters based on gender perspectives. Data were collected through interviews, participatory observation, and documentation. Using a multisite constant-comparative method, this study involved headmasters, supervisors, teachers, administrative staff, parents and society. The qualitative analysis of the data resulted in the findings that female headmasters were effective in their leadership although they were a bit slow in responding to innovations.